Nonlinear dynamic characteristics of wind power concentric planetary-face gear system with elastic lubrication and friction considering thermal effect under random wind load - Xincheng, Bi; Jungang, Wang; Ruina, Mo (Frontiers in Physics, 2024)
IntroductionPlanetary-face gears combine the advantages of both planetary and face gears, offering potential value for wind power applications. During the gear meshing process, a large amount of heat is generated, and tooth wear also occurs, which affects transmission performance.MethodsAnalyzing multiple factors such as lubrication performance and thermal effects of meshing pairs plays a crucial role in improving the overall lifespan of transmission systems. This study developed a nonlinear dynamic model of a wind power planetary-face gear system, considering factors like random wind load, tooth surface friction, temperature rise, tooth side clearance, and elastic lubrication. Nonlinear methods such as bifurcation diagram, maximum Lyapunov exponent diagram, and time-frequency diagram were used to analyze the effects of wind turbine radius, average wind load, temperature rise, and lubricant viscosity on the dynamic response of the gear transmission system under random wind loads.ResultsThe results show that selecting an appropriate wind turbine radius for different wind loads is essential to enhance system stability. Higher lubricant viscosity can suppress chaotic phenomena in gear systems. For a well lubricated gear system, tooth surface temperature rise is a key factor affecting the dynamic characteristics of the system.DiscussionThis article aims to provide valuable insights into improving the operational stability of the wind turbine planetary gear system.